Azas Keadilan dalam Ilmu Mawarist Perspektif Hukum Islam dan Hukum Perdata dan Hukum Adat - Fajri, Muhammad; Rapi, Ahmad; Perdiansyah, Restu Ilham; Sari, Windy Kartika; Syamsiah, Syamsiah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
The implementation of inheritance law must be based on the principles of order and justice in the process of transferring the property of the heirs to the heirs who are in one family. Therefore, in determining the distribution of inheritance, there are three legal perspectives used, namely Islamic inheritance law, civil inheritance law, and customary inheritance law, all of which prioritize the principle of balanced justice. This is so that the distribution of inheritance can be done fairly between the heirs. The approach in this study uses a normative juridical method, with a doctrinal approach that refers to laws and regulations. The source of this research comes from secondary data obtained through the study of legal materials and literature. This study aims to analyze the legal basis used in applying the principle of justice in the perspective of Islamic inheritance law, civil inheritance law, and customary inheritance law in Indonesia. In Indonesia, there are three systems of inheritance law that apply, namely Islamic inheritance law, customary inheritance law, and civil inheritance law, which are accepted in Indonesian legal society. Based on the results of the research, the division of inheritance according to the three legal systems shows differences. First, according to Islamic inheritance law, the share of inheritance received by men is greater than that of women, which is 2:1, because men have a greater responsibility. Second, in civil inheritance law, the principle of justice is applied by dividing the inheritance equally between men and women in terms of rights and obligations. Third, in customary law, the distribution of inheritance varies depending on the customs of each region.